Respostas

A melhor resposta!
  • Usuário do Brainly
2014-07-09T19:05:15-03:00
A)
3 \sqrt{20} - \frac{3 \sqrt{45} }{2} + \frac{2 \sqrt{125} }{3} - \sqrt{245} =

3 \sqrt{ 2.5^{2} } - \frac{3 \sqrt{3 ^{2},5 } }{y} + \frac{2 \sqrt{ 5.5^{2} } }{3} - \sqrt{ 7.5^{2} } =

 6 \sqrt{5} - 9\frac{ \sqrt{5} }{2} + \frac{10 \sqrt{5} }{3} -7 \sqrt{5} =

( 6^{} - \frac{9}{2} + \frac{10}{3} -7) \sqrt{5}

( \frac{36-27+20-42}{6} ) \sqrt{5}

 \frac{-13 \sqrt{5} }{6}

b)
(2√3-5√2)²=

(2√3)²-2(.2√3.5√2)+(5√2)²=

4.3-20√6 +25.2=
12-20√6+50=

62-20√6
2 5 2